Activation Level and Probabilities of Electromagnetic γ-transitions in the Reaction 77Se(γ,γ’)77mSe - Viktor Zhaba; Eduard Gohman (Emerging Science Journal, 2020)
The dependence of the absolute yield from energies for reaction (γ,γ’)m on the nucleus 77Se was approximated by fit dependences (lines). Due to the visually detected fracture of the reaction yield, the energy interval 5.75-8.0 MeV is conventionally divided into two parts. For the transition step as one experimental point, the left part was approximated to 6.6 MeV, and the right part - from 6.26 MeV. There approximations were eight for both intervals. Given the features of the calculation and the minimum values for χ2, the "best" two fits are approximation dependences in the neighborhood of the intersection point x0 for the left and right arrays of energies. The energy for the activation level (the intersection point for these functions) is Ea≈6.35 MeV. The scheme of electromagnetic γ- transitions for nucleus 77Se are constructed and analyzed. Possible transitions to the isomeric level from higher levels are indicated. Weiskopf model was used to estimate the values of the reduced probabilities of electric EJ- and magnetic MJ- transitions, the probabilities of transitions per unit time and half-life. The theoretical values of the half-lives T1/2 are compared with the experimental data. Prospects for further use of the obtained results for topical problems of nuclear physics are discussed.